Creating Visual Identity in Film Festival Designs - KARAALİOĞLU, SEVİM (Deniz Yengin, 2025)
Throughout history, people have come together to organize various celebrations and festivals. Festivals are events that carry a universal significance, fostering a sense of unity and shared emotions. In particular, film festivals, whose importance has grown significantly in recent times, serve as a reflection of cultural values, societal lifestyles, emotions, and ideas. These events, characterized by rich content and diversity, and with artistic expression at the forefront, highlight the significance of the work done in the field. In this context, a strong and effective visual identity is essential in the creation of the festival’s identity. Cultural codes, symbols, visuals, color, typography, form, and shape play a critical role in constructing the festival’s character. This study, employing qualitative research methods, examines the corporate identity designs of the 74th Berlin International Film Festival and the 43rd Istanbul Film Festival, emphasizing the importance of creating a visual identity for film festivals. These analyses are conducted through a semiotic approach. A literature review was also conducted, and the selected film festival designs were descriptively analyzed in terms of design elements such as color, typography, visual impact, coherence, and form-content harmony. The aim of this study is to identify the descriptive challenges faced in the visual identity creation process and propose solutions to address these issues. Given the limited number of academic studies in the field, this research is expected to contribute to the existing literature.
Keywords: Festival; Film Festival; Design; Visual Design; Visual Identity